2021
DOI: 10.7554/elife.60830
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised changes in core object recognition behavior are predicted by neural plasticity in inferior temporal cortex

Abstract: Temporal continuity of object identity is a feature of natural visual input, and is potentially exploited -- in an unsupervised manner -- by the ventral visual stream to build the neural representation in inferior temporal (IT) cortex. Here we investigated whether plasticity of individual IT neurons underlies human core-object-recognition behavioral changes induced with unsupervised visual experience. We built a single-neuron plasticity model combined with a previously established IT population-to-recognition-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 87 publications
(268 reference statements)
0
4
0
Order By: Relevance
“…Recognizing a new unfamiliar object as the same single object across different view angles is difficult if object images show a drastic change, particularly when a subject is required to distinguish it from similar distractors. However, view‐invariant object recognition can be acquired gradually via the neural population of the inferotemporal (IT) cortex of the ventral pathway as a subject repeatedly sees the objects from different views (Jia et al, 2021; Logothetis et al, 1994; Okamura et al, 2014). Thus, we can reasonably hypothesize that an association is made between various background images viewed from different self‐positions to represent the same objective‐position in the environment.…”
Section: Allocentric Perceptual Information Supported By View‐center ...mentioning
confidence: 99%
“…Recognizing a new unfamiliar object as the same single object across different view angles is difficult if object images show a drastic change, particularly when a subject is required to distinguish it from similar distractors. However, view‐invariant object recognition can be acquired gradually via the neural population of the inferotemporal (IT) cortex of the ventral pathway as a subject repeatedly sees the objects from different views (Jia et al, 2021; Logothetis et al, 1994; Okamura et al, 2014). Thus, we can reasonably hypothesize that an association is made between various background images viewed from different self‐positions to represent the same objective‐position in the environment.…”
Section: Allocentric Perceptual Information Supported By View‐center ...mentioning
confidence: 99%
“…Pioneering work by Simoncelli and Olshausen (2001) showed that natural image statistics shape V1-like response patterns in artificial neural networks. Furthermore, electrophysiological studies have captured an unsupervised change of representation in IT neurons in a manner dependent on the visual experience ( Li and DiCarlo, 2010 ; Jia et al, 2021 ). Together with these results, we consider that the visual system may have the ability to shape its own activity depending on its input statistics, even in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…lITG is a high-level brain area of the ventral visual pathway, which is related to the position, color, posture, and facial recognition of objects. lITG is a brain region that is arguably central for visual object recognition in both humans and nonhuman primates (Li and DiCarlo, 2008;Jia et al, 2021). In a fMRI study of table tennis players on a visuospatial task, Guo et al found that athletes exhibited lower brain activation in the regions of the left MTG, bilateral lingual gyrus, and lITG than non-athletes (Guo et al, 2017).…”
Section: Relationship Between the Higher Neural Efficiency Of The Vis...mentioning
confidence: 99%